2018
DOI: 10.1071/am17046
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction of the greater stick-nest rat (Leporillus conditor) to Heirisson Prong, Shark Bay: an unsuccessful attempt to establish a mainland population

Abstract: Greater stick-nest rats were reintroduced to Heirisson Prong from Salutation Island at Shark Bay to establish the first mainland population in Western Australia in over 60 years. Forty-eight animals were transferred over two years from August 1999 to a 17-ha enclosure of natural vegetation that excluded foxes and feral cats. This refuge from introduced predators was located within a larger 1200-ha area where these predators were controlled. Stick-nest rats were able to disperse from the refuge to the wider are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Leporillus conditor has been used in several translocation programs in recent decades, with the Franklin Islands population acting as the primary source (Pedler and Copley 1993;Short et al 2018Short et al , 2019White et al 2018). Our analyses show that these individuals are likely larger than their extinct counterparts in most mainland locations, with the exception of central Australia.…”
Section: Implications For Translocationmentioning
confidence: 72%
“…Leporillus conditor has been used in several translocation programs in recent decades, with the Franklin Islands population acting as the primary source (Pedler and Copley 1993;Short et al 2018Short et al , 2019White et al 2018). Our analyses show that these individuals are likely larger than their extinct counterparts in most mainland locations, with the exception of central Australia.…”
Section: Implications For Translocationmentioning
confidence: 72%
“…However, L. conditor may favour L. ferocissimum bushes because the large thorns provide more protection from predators than the plants that are native to the animal's offshore island refuges. A preference for thorns and spines by L. conditor is supported by Short et al (2018) who found that very prickly Acacia tetragonophylla bushes were the primary nesting shrubs used by L. conditor at Heirisson Prong (Introduced in 1999, last sighting in 2007), in Shark Bay, Western Australia.…”
Section: Discussionmentioning
confidence: 92%
“…Successful translocations occurred in novel ecosystems on St Peter Island and Reevesby Island in South Australia, and Salutation Island in Western Australia, which are free from feral predators such as cats and foxes (Copley 1999a). The success of this recovery plan resulted in the down-listing of this species' conservation status from 'Endangered' in 1996to 'Vulnerable' in 2008to 'Near Threatened' in 2016 the IUCN Red List of Threatened Species (Short et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous attempts, none of these species have been successfully established into their former ranges without the protection of predator-free fenced areas or islands (Bannister et al 2016;Moseby et al 2018). While there might be hope for some (West et al 2018), it seems that most of these vulnerable species do not have the life histories or behavioural strategies that will allow them to ever coexist with introduced predators (Short et al 2018). For these animals, conservation fences coupled with the eradication of introduced predators are often the only thing standing between them and extinction in the wild (Fig.…”
Section: Land Management (Fences and Barriers)mentioning
confidence: 99%